RITUAL â€œKLIWONANâ€ BAGI MASYARAKAT BATANG - Widyatwati, Ken (Faculty of Humanities, Diponegoro University, 2013)
ABSTRACT The narrative has a meaning and structure. The structure of kinwonan myth is representation from the society, who to support. Structure or model to become representation from the society to exist in stage unconscious, and only to be looking for with structuralism Levi-Straus Analysis. The aim of this research is descriptions of kliwonan Ritual for Batang Society are component Identification, and the content of myth. This Ritual performs every Jumat Kliwon day in Javanese Calendar. Time is 14.00-18.00 am. The place is Alun-alun Batang, Central Java. The content of Exorcism Ritual for Dieng Society is place, time, instrument, ritual offering, prayer and myth. This myth is jumat kliwon and kliwonan Ritual. Keyword: Ritual, Kliwonan Ritual Procession.